Employees’ Career Transition and Growth: A Study of Women-Owned Micro Businesses in Balogun Market, Lagos, Nigeria - Obunike Chinazor Lady-Franca (Economics and Business)
The study aims at investigating the effect of voluntary career transition on women-owned micro business growth. The independent variable ‘voluntary career transition’ is used as a single construct while the dependent variable ‘business growth’ is decomposed as a multi-construct of sales, employees and assets growth. The population of the study comprises 384 persons, while the sample size used is 250 micro businesses owned by women, who are formal employees of organisations. Average distribution is used to select the number of questionnaires that were distributed by the ten lines of business selected for the study. The study employs self-constructed questionnaire items to measure the independent, while an adopted questionnaire is used for firm growth. Frequencies and descriptive statistics are used to analyse the data collected from 104 questionnaire respondents, while the regression analysis is used to test the hypotheses. The findings indicate that voluntary career transition has a very high positive effect on the employment creation, a high positive effect on the sales growth and a very low positive effect on the asset growth of the business under study. The study, therefore, concludes that although carrier transition from paid employment to micro-businesses might be a difficult carrier choice and unattractive decision, for most women, it has been proven to be a contributing factor that affects the growth of women micro business. The study, therefore, suggests that organisational management and policymakers should encourage intrapreneurs and micro businesses.